Factors that influence negative summation in a spatial-search task with pigeons - Leising, Kenneth J. (2012)
A variant of the standard conditioned inhibition procedure was used to evaluate landmark-based spatial search in a touchscreen preparation. Pigeons were given compound trials with one landmark (A) positioned in a consistent spatial relationship to a hidden goal and another landmark (B) positioned randomly with respect to A and the hidden goal (AB+). On half of the non-reinforced inhibitory trials, A was paired with landmark X (AX−) and on the remaining trials B was paired with Y (BY−). All subjects were also given reinforced trials with a transfer excitor (T+). During conditioned inhibition training, subjects showed no change in overall responding during AX− trials but did show a decrease in the number of pecks to the goal location signaled by A. During non-reinforced summation tests with landmark T, X had a greater suppressive effect than did Y on overall responding but the percentage of pecks at the goal did not differ unless X was positioned near the expected goal signaled by T. These data demonstrate that the effectiveness of a stimulus trained as an inhibitor is dependent on the strength of the association between its training excitor (A) and the US, as well as, the spatial arrangement of stimuli during testing.